Gamification Strategy with Escape Rooms: Experience in the Cataloging I Laboratory Courses at the School of Library and Information Science of the University of Costa Rica - Calvo Chaves, Valeria (2025)
The present research aims to evaluate the level of acceptance of the escape room gamification strategy implemented in the course Laboratory of Cataloging I during the first semester of 2024, considering its effectiveness as a playful learning tool. The research follows a mixed-methods approach, combining quantitative and qualitative methods, including experiences, observations, surveys, and statistical analysis. In the context of escape rooms, a descriptive and exploratory methodology is employed: situations and problems are described to contextualize learning, and the limited information available on gamification in the bibliographic field is addressed. Overall educational experiences can improve with innovative strategies; most students agreed that the escape room gamification strategy was motivating compared to the monotony of traditional classes. This suggests that dynamic and novel activities stimulate student interest and engagement. The gamification teaching strategy positively captured attention, fostering both active participation and the development of practical skills and competencies necessary for students' future professional careers. Innovative strategies, such as gamification, enrich traditional teaching methods.